Energy Transfer between Fluorescein Isothiocyanate and Propidium Iodide – A Problem in the Estimation of Tpot with the Bromodeoxyuridine–DNA Flow Cytometry Technique? - Maria C. Johansson; Bo Baldetorp; Stina M. Oredsson (Analytical Cellular Pathology)
Energy transfer in flow cytometry can occur when two fluorochromes are bound in close proximity (generally within 100 Å) and the emission spectrum of one fluorochrome overlaps significantly with the excitation spectrum of the other. The latter criterium is fullfilled for the fluorochromes fluorescein isothiocyanate and propidium iodide and also the former when they, e.g., are used in bromodeoxyuridine – DNA flow cytometry methods. In the present growth kinetic study using this method, we show that energy transfer does take place between fluorescein isothiocyanate and propidium iodide which results in a detected increase in DNA content with 2–3%. Despite the erroneous increase in the obtained DNA content values, this does not seem to have any influence on the calculation of DNA synthesis time and potential doubling time where the DNA content, based on the relative movement principle of the labelled cells, is used.